Experience of deinstitutionalisation from service users’ perspective in Croatia - Šajfar, Petar (Socialno delo, 2023)
As in other post-socialist countries, the process of deinstitutionalisation in Croatia began much later than in Western countries. A turning point is the year 2014, when the mass relocations of people with intellectual disabilities from long-term institutions to community-based settings began. The focus of this research is on the experiences of deinstitutionalisation from the perspective of service users. The research methodology is based on a qualitative approach because it enables a deeper understanding of the problem and allows the researcher to focus on real life experience of respondents. The sample included 27 participants (14 males, 13 females) who during the research lived in 11 different group homes in different parts of the Republic of Croatia. Based on thematic analyse, the results show that the majority of respondents had to move from a long-term institution to a group home due to necessity when long-term institutions were closed. The criteria by which someone was selected or excluded for admission to the deinstitutionalisation process was his or her functionality (e.g. good behaviour, physical mobility). Finally, the research shows that most participants were not systematically and purposefully prepared for the transition from a long-term institution to a group home. Findings of the study are partly in line with the international literature, highlighting the marginal role and difficulties of service users in the deinstitutionalisation process.
Keywords: community-based support; deinstitucionalizacija; dolgotrajna oskrba; group homes; intelektualne ovire; intellectual disability; long-term care; podpora v skupnosti; preselitev; relocation; stanovanjske skupine